2019
DOI: 10.1111/1759-7714.13046
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of KLF5 promotes cisplatin‐induced cell apoptosis via regulating DNA damage checkpoint proteins in non‐small cell lung cancer

Abstract: Background Previous research has revealed that Krüppel‐like factor 5 ( KLF5 ) may affect DNA damage repair pathways; however, the associated molecular mechanisms are unclear. Methods The expression of KLF5 was studied by immunohistochemical staining in paired tumour and normal tissues from 90 patients with ESCC. We studied the effects of KLF5 knockdown on cell proliferation and apoptosis wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…A previous study has revealed, in a small number of PTC tumor samples, an association between KLF5 and lymphnode metastasis, but not other clinical parameters, which could be due to the small number of patient samples in their cohort [ 10 ]. The prognostic significance of KLF5 upregulation seen in our cohort is similar to previously reported studies in other organ sites, like pancreatic [ 6 ], gastric [ 18 ] and lung cancers [ 19 ]. However, KLF5 upregulation is not an independent prognostic factor in multivariant analysis.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study has revealed, in a small number of PTC tumor samples, an association between KLF5 and lymphnode metastasis, but not other clinical parameters, which could be due to the small number of patient samples in their cohort [ 10 ]. The prognostic significance of KLF5 upregulation seen in our cohort is similar to previously reported studies in other organ sites, like pancreatic [ 6 ], gastric [ 18 ] and lung cancers [ 19 ]. However, KLF5 upregulation is not an independent prognostic factor in multivariant analysis.…”
Section: Discussionsupporting
confidence: 91%
“…In vitro, chemotherapy combined with Chk1 inhibitor can significantly reduce the survival rate of NSCLC stem cell [54]. Targeting Chk2 reduced phosphorylation and increased the efficacy of cisplatin [55]. Researches showed that genomic changes of IRS1 could lead to development of lung cancer [56].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the LRSI group, KLF5 was the most significant gene for CNV in the HRSI group. KLF5 plays an important role in the DNA damage response by regulating DNA damage checkpoint proteins and is associated with cisplatin DDP resistance [ 33 35 ]. The relationship between KLF5 and radiotherapy sensitivity needs to be discovered.…”
Section: Discussionmentioning
confidence: 99%